Bibliometric analysis of scientific development in countries of the Union of South American Nations (Unasur) - Greco, Andres Francisco (2012)
The Union of South American Nations (Unasur) can be considered as a new emergent region in the world. By using advanced bibliometric methods, the development of science and technology in Unasur is explored. Based on data from the InCites tool of Thomson Reuters, which facilitates national comparisons across long time periods using publication output and normalized citation impact values, we explored how this region (particularly the most productive individual countries within it) is developing. The publication output results reveal an increase in the scientific and technological activities in most of the Unasur countries (especially Brazil). Compared to the rest of the world, the citation impact trend is less favourable for all Unasur countries.